An Advance Letter Did Not Increase the Response Rate in a Telephone Survey: a Randomized Trial - Carey, R.; Reid, Alison; Driscoll, T.; Glass, D.; Benke, G.; Fritschi, Lin (Elsevier, 2013)
Objective: To test the impact of an advance letter on response and cooperation rates in a nationwide telephone survey, given previous inconsistent results.Study Design and Setting: Within the context of a larger telephone survey, 1,000 Australian households were randomly selected to take part in this trial. Half were randomly allocated to receive an advance letter, whereas the remainder did not receive any advance communication. Response and cooperation rates were compared between the two groups.Results: A total of 244 interviews were completed, 134 of which were with households that had been sent an advance letter. Intentionto-treat analysis revealed no significant difference in response between those who had received a letter and those who had not (26.8% vs. 22.0%, respectively). In addition, there was no significant difference between the groups in terms of either cooperation (78.4% vs. 79.7%) or response rate (56.3% vs. 57.9%), and no clear differences emerged in terms of the demographic characteristics of the two groups.Conclusion: An advance letter was not seen to be effective in increasing response or cooperation rates in a nationwide telephone survey. Researchers should consider alternative methods of increasing participation in telephone surveys.